THREATS TO GOLDEN-FLOWERED CAMELLIAS ALONG HON GIAO PASS - S. Curry Anthony (Tạp chí Khoa học Đại học Đà Lạt)
The identification, documentation, and discussion of the main threats affecting the golden-flowered Camellia species endemic to Hon Giao Pass are discussed. Observations, published literature, and collations of data accumulated from field trips throughout Vietnam since 1999 are analyzed and researched for the preparation of the article. The major anthropogenic risk factors affecting the golden-flowered Camellia species and their habitats on the Dalat Plateau and along the Hon Giao Pass are named and reviewed. These risk factors include habitat loss due to population growth, logging, habitat fragmentation and degradation, poaching, collection of wild plant species, fire, and the construction of dams and their associated water impoundments.